Wood Waste Utilization in the Forest Industry: Innovations for Sustainable Management - , Shivendra Verma; , Rajesh Kumar; , Bhuvan Singh; , Chetna Sahu; , Pallavi Soni; , Sandeep Chetan; , Pradip Mohale; , Raman Choudhary; , Gulendri Netam; , Himanshu Khandekar; , Alok Singh Bargah; , Aishwary Kant Vaishnav (Archives of Current Research International, 2025)
The forestry sector produces considerable quantities of wood waste throughout the processes of harvesting, processing, and manufacturing. This waste poses a significant environmental challenge, leading to greenhouse gas emissions, the accumulation of waste in landfills, and the depletion of resources. The investigation data was collected in literature review and case studies of the related field. This study aims to analyse the challenges and opportunities related to the utilization of wood waste, emphasizing innovative technologies and strategies for sustainable management. We analyse both current and emerging uses of wood waste, such as bioenergy generation, composite materials, wood-derived chemicals, and soil enhancements. The study identifies integrated biorefineries and technological innovation as critical pathways for enhancing wood waste value.